Technological audiovisual aids in the subject Advanced Intensive English II of 3rd year of the Foreign Languages Department in the University of El Salvador, semester I 2012 - Hernández Funes, Edna Verenice; Lima Ramírez, Juan Alberto; Meléndez Rivera, María José; Garay Salinas, Ricardo; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2013)
All along this project, it is going to be presented significant information about how audiovisual aids were born and how they have been developed through the years, likewise how its use has been incorporated into the daily lives of students and teachers. Also, this useful research will give a better understanding of which are the most used technological audiovisual aids in the Foreign Languages Department as well as their effectiveness. On the other hand, it could help teachers to know more about the use of these tools in classes and provide better teaching through them. Besides that, it is taken into consideration not only the use but also which are the audio visual aids available in the Foreign Language Department, the frequency with which they are used by teachers and the impact of those in students. Finally, with the information gathered, it is expected to benefit the Foreign Languages Department with valuable and accurate information to promote the use of audiovisual aids and request updated equipment in order to deal with this competitive world
Anexos: instrumentos de la investigación.
Tesis -- (Licenciatura en Lenguas Modernas especialidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2013
Referencias : hoja 48
La tesis está en formato digital.
Keywords: Inglés -- Enseñanza; Tecnología educativa; Medios audiovisuales